Chitosan-based hydrogel tissue scaffolds made by 3D plotting promotes osteoblast proliferation and mineralization. (13th May 2015) - Liu, I-Hsin; Chang, Shih-Hsin; Lin, Hsin-Yi
Abstract: A 3D plotting system was used to make chitosan-based tissue scaffolds with interconnected pores using pure chitosan (C) and chitosan cross-linked with pectin (CP) and genipin (CG). A freeze-dried chitosan scaffold (CF/D ) was made to compare with C, to observe the effects of structural differences. The fiber size, pore size, porosity, compression strength, swelling ratio, drug release efficacy, and cumulative weight loss of the scaffolds were measured. Osteoblasts were cultured on the scaffolds and their proliferation, type I collagen production, alkaline phosphatase activity, calcium deposition, and morphology were observed. C had a lower swelling ratio, degradation, porosity and drug release efficacy and a higher compressional stiffness and cell proliferation compared to CF/D ( p  < 0.05). Of the 3D-plotted samples, cells on CP exhibited the highest degree of mineralization after 21 d ( p  < 0.05). CP also had the highest swelling ratio and fastest drug release, followed by C and CG ( p  < 0.05). Both CP and CG were stiffer and degraded more slowly in saline solution than C ( p  < 0.05). In summary, 3D-plotted scaffolds were stronger, less likely to degrade and better promoted osteoblast cell proliferation in vitro compared to the freeze-dried scaffolds. C, CP and CG were structurally similar, and the different crosslinking caused significant changes in their physical and biological performances.